Knowledge on home management of diarrhea among caregivers of children below five years with diarrhea in Ngandu Location, Nyeri County, Kenya - Gathogo, Leah Wambui; Oluchina, Sherry; Mwangi, Elijah (International Journal Of Community Medicine And Public Health, 2020)
Background: To prevent dehydration and malnutrition in children with diarrhea, it is important they get good management at home. The caregivers should commence home remedies immediately before they seek medical advice. This study assessed the level of knowledge on home management of diarrhea among caregivers of children below five years with diarrhea. Methods: This research applied descriptive cross-sectional study design. The current study was a household survey targeting caregivers of children below five years with diarrhea. The Cochran's sample size formula was used to calculate a sample size of 345 respondents. Purposive sampling was used to recruit respondents in the study. The study employed a researcher- administered semi-structured questionnaire and use of a checklist. Descriptive statistics and chi-square tests were used in the analysis. Results: The study found that that slightly above half 52.2% (n=180) of the respondents had low knowledge on management of diarrhea. There was a significant relationship (χ2=4.044, df=1, p<0.044) between respondent’s’ level of education and knowledge of home management of diarrhea. Cross tabulation showed that 60.2% of those who had low education also had low knowledge. Conclusions: The study concluded that the level of knowledge on home management of diarrhea among caregivers of children below five years with diarrhea was low. Level of education was a significant predictor of knowledge whereby low knowledge was associated with low education. The study recommends enhanced education of mothers on home management of diarrhea by nurses.